Heritage Protection versus Individual Interests in a Post-Socialist Country: the Case of Mšeno, Czech Republic - Nowotny, Vojta; Wranová, Alena; Trevisan, Jitka (European Spatial Research and Policy, 2015)
Large-scale investment is routinely believed to be the main danger to urban heritage. The measures designed to sustain heritage thus traditionally focus on steering investment into respectful ways of real-estate development. The majority of Czech built heritage is, however, located in towns and villages that rather face economic decline. Losses of objects of heritage in such places are often due to lack of maintenance. The case study of this article discusses the issues of heritage protection and restoration of the Enlisted town zone of Mšeno, where affordability and communication of values are the key issues in heritage protection.